Effect of Work Discipline and Motivation on Employee Performance of Sewing Departement at PT Adis Dimension Footwear Kabupaten Tangerang - Zaludin, Syafri; Purwanto, Agus; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of work discipline on employee performance; (2) the partial effect of motivation on employee performance; (3) the simultaneous effect of work discipline and motivation on employee performance. This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all production employees at PT. Adis Dimension Footwear Balaraja Tangerang. The research sample consisted of 80 respondents. Simple random sampling was used to determine the sample size. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis using SPSS 26. The results of this study indicate that (1) partially, work discipline significantly influences t on the performance of Sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (4.230 > 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, motivation significantly influences the performance of Sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (2.680 > 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work discipline and motivation significantly influence the performance of Sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by F count > F table (42.055 > 3.12) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that work discipline and motivation variables, both partially and simultaneously, have a significant influence on the performance of sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang.